International Practice of Innovative Technologies of Project Financing - Holovnia Olena M. (Bìznes Inform, 2021)
In today’s world, the international community provides significant support in carrying out socio-economic and political reforms to countries that need it. Such support is provided in the form of official aid for the purposes of development, which includes international technical and humanitarian assistance, loans for repayment of foreign debt on preferential terms, financing of project activities. The article analyzes the state of Ukraine’s cooperation with international financial organizations in providing financial and technical assistance for the implementation of projects that are of great importance for structural reforms of the domestic economy. The national economy of Ukraine has been experiencing a lasting shortage of financial resources necessary for innovation and investment development projects, also for current needs of the State. Given the difficulties of mobilizing free cash in the domestic capital market, Ukraine attracts resources in foreign markets. Expanding partnerships with international donor organizations allows not only to find additional sources of funding for projects aimed at socio-economic and humanitarian development, but also to provide real help to those in need. The implementation of joint projects and programs involving communities and local authorities in practice makes it possible to gain useful and important experience based on the best world and European practices. It is examined that in the national economy the urgent problem is the search for new types of interaction between communities to solve socially important issues, including the search for unconventional sources of financing. To a large extent, the search for and involvement of funds in the social sphere is facilitated by innovative technologies for financing social development – fundraising, crowdsourcing and crowdfunding platforms, which are manifestations of social communications and become relevant in the context of decentralization and community development.